A comparison of sedimentological, environmental and fauna between two regions, NW of the Arabian Gulf - Al-Humaidan, Zainab A.; Al-Jaberi, Mohanad H.; Al-Ali, Rasha A. (Mesopotamian Journal of Marine Sciences, 2019)
Marine environment is considered one of the richest environments in fauna of benthic marine micropaleontology because of the suitable conditions for living requirements like food, oxygen, sediment texture and salinity. In the current study, a fauna and their distribution were studied according to the depths of subsurface marine sediments from two regions at the NW Arabian Gulf, the first region at Khor Shytanah (Core 1) at the north of the study area representing a sever environment with high currents, and contain more than 95% sand grains, it is of light color, large size, rounded to sub-rounded grains and clean due to the continuous washing and water movement, whereas the second region was near the oil Basrah Port (Core 2) at the south of the study area, where the quite environment with weak currents and fine sand of dark color due to the activity of non-anaerobic bacteria , the region has angular to sub-angular grains. The type of sediment texture was determined at each depth and consisted of silt, sand silt, sand and silty sand. On the other hand, the percentage of calcium carbonate was determined in the sediments to correlates that with the size and density of fauna that live in this area.